Grammar phobia as a hindrance to the fluency in oral communication of Bangladeshi tertiary level students: A study - Md Mahmud Hasan Chowdhury (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
Oral communication has a highly significant role to stay in touch with the current global circumstances, but a low level of speaking fluency is seemingly a major drawback for Bangladeshi tertiary-level students to achieve global standards of speaking. Taking the core issue into account, this study aims to explore grammar phobia as an obstacle to the learners’ way of gaining fluency in oral communication. To substantiate the hypothesis a fact-finding survey for the study has been conducted on the learners of the tertiary level of a particular region in Bangladesh. The findings of the study show grammar phobia of the learners as a major threat to fluency as they get less exposure to free expression and communication when it comes to mutual interaction in the classes. In a typical Bangladeshi approach to language learning, the learners are supposed to put extra emphasis on grammatical accuracy for communicative competence, but most of them admitted that they fumble in free fair communication for fear of grammatical issues. In addition, It would be further evident from the study that teachers’ limitations and lack of expertise contribute to the overall failure of tertiary-level learners in their performances in oral communication.DOI: 10.26905/enjourme.v7i2.8767